Uric acid is associated with vascular dementia in Chinese population. Issue 2 (5th December 2016) - Xu, Yuzhen; Wang, Qian; Cui, Ruiting; Lu, Kaili; Liu, Yunlin; Zhao, Yuwu
Abstract: Objective: Mounting evidence suggests that oxidative stress is involved in the pathogenesis of vascular dementia (VD). Uric acid (UA) has long been implicated as a critical cause of cardiovascular disease. Nevertheless, UA was also expected to play an important role in antioxidant and neuroprotection recently. We hypothesized that UA may have a protective role against VD. The aim of this study was to investigate the link between serum UA and cognitive dysfunction in VD. Materials and Methods: There were altogether 127 VD subjects and 81 nondemented controls enrolled in our study. Serum UA, demographic, and clinical characteristics were recorded at baseline, and all participants underwent Mini‐Mental State Examination (MMSE) at the beginning of the trial. Results: The VD group showed lower MMSE scores and serum UA levels than nondemented controls and there was significant statistical difference between the two groups ( p  < .05). Demographic and clinical characteristics such as age, gender, education, body mass index (BMI), total cholesterol (TC), triglycerides (TG), high‐density lipoprotein cholesterol (HDL), low‐density lipoprotein cholesterol (LDL), blood urea nitrogen (BUN), and serum creatinine (Scr) did not differ dramatically between groups ( p  > .05). In VD subjects, there was a positive correlation between serum UA and MMSE scores ( r  = .32, p  <   .05), and this correlation was independent of demographic and clinical characteristics (β = .272, p  <   .05). Conclusions: VD subjects have dramatically lower serum UA levels in comparison to nondemented controls. Lower serum UA levels are linked to cognitive dysfunction and could serve as a potential predictor for VD. Abstract : The association of uric acid levels and Alzheimer's disease has been widely addressed, but limited relative data exist regarding vascular dementia. Our results showed that vascular dementia patients had lower serum uric acid levels than control subjects. In addition, we also found that serum uric acid levels were positively correlated with MMSE scores and the association was independent of confounding factors in vascular dementia patients. Our study is the first study on the relation between uric acid and vascular dementia in Chinese population. The relationship between uric acid and vascular dementia, if confirmed by future research, may have critical clinical and therapeutic implications.